PENGARUH STRESS KERJA TERHADAP KINERJA KARYAWAN - Devina Nur Oktaviani; Nur Irmayanti (PSIKOWIPA (Psikologi Wijaya Putra), 2021)
Employee performance is the work of individuals in carrying out their duties, responsibilities and demands set by the company to achieve job requirements that have been determined by the company. Factors that can affect performance are work stress, physical, health, work environment, climate, length of time working, knowledge and skills. This study aims to determine the effect of work stress with employee performance. The dat research method used is product moment correlation by testing the work stress scale and employee performance scale. Based on the calculation results obtained the value of the correlation coefficient (rxy) of -0.158; p > 0.272. By using the significant limit = 0.05, we get an R table of 0.273. From these results, the test criteria are R count < R table -0.158 < 0.273, which means Ho is accepted and Ha is rejected. Thus, the product moment correlation test hypothesis on teh work stress variable has a negative and significant effect on employee performance.